Political extremism, conflict identities and the search for ontological security in contemporary established democracies - Rich, Ben (Academia.edu, 2021)
This paper argues that a key element driving political instability and politically extreme movements in contemporary liberal democracies is found in the search for ontological security by groups disaffected under globalisation and the uncertain conditions of late modernity. It suggests that in many cases, such organisations have found a panacea to anxieties generated by these processes in hardened identities based primarily on fighting for their own survival against the perceived existing political, social and cultural order